Substantiating democratic decentralisation through free and fair elections: Case of local bodies' elections in Tamil Nadu - Palanithurai, G. (2013)
Panchayati raj institutions represent the vigour of democratic functioning at the grassroots. Although the gram panchayats constitute the lowest rung in the political network, the elected members play an important role not merely in the elections to the taluk and the zilla panchayats but also to the legislature as well. According to the Panchayati Raj Act elections to the PRIs should be strictly conducted on apolitical lines, but political parties do get involved overtly or covertly. The people also participate in these elections with the same enthusiasm and involvement which they display in the elections to the Parliament or state assemblies. Yet the local body elections are much complicated and complex than the elections to national or state legislatures. - Reproduced.
Keywords: Decentralization; Elections